2021
DOI: 10.1371/journal.pone.0245849
|View full text |Cite
|
Sign up to set email alerts
|

Inter-identity amnesia for neutral episodic self-referential and autobiographical memory in Dissociative Identity Disorder: An assessment of recall and recognition

Abstract: Amnesia is a core diagnostic criterion for Dissociative Identity Disorder (DID), however previous research has indicated memory transfer. As DID has been conceptualised as being a disorder of distinct identities, in this experiment, behavioral tasks were used to assess the nature of amnesia for episodic 1) self-referential and 2) autobiographical memories across identities. Nineteen DID participants, 16 DID simulators, 21 partial information, and 20 full information comparison participants from the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
2
0
3
Order By: Relevance
“…Os psicólogos do estudo, ulilizaram Dissociative Experiences Scale (DES), the PTSD Symptom Scale-Self-Report (PSS-SR) e uma escala de avaliação da emoção. Os resultados indicam que o perfil de desempenho do TDI não foi contabilizado por amnésia verdadeira ou fingida, dando suporte à ideia de que a amnésia relatada pode ser mais percebida do que o prejuízo real de memória (MARSH, 2021).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os psicólogos do estudo, ulilizaram Dissociative Experiences Scale (DES), the PTSD Symptom Scale-Self-Report (PSS-SR) e uma escala de avaliação da emoção. Os resultados indicam que o perfil de desempenho do TDI não foi contabilizado por amnésia verdadeira ou fingida, dando suporte à ideia de que a amnésia relatada pode ser mais percebida do que o prejuízo real de memória (MARSH, 2021).…”
Section: Discussionunclassified
“…Alguns psiquiatras não partilham de mesma opinião sobre o diagnóstico de TDI, pois consideram que o TDI se encaixa em um quadro de psicose ou histeria, onde a pessoa começa a ter delírios durante suas crises (FARIA, 2019). O diagnóstico das doenças dissociativas depende principalmente dos laudos do paciente e do relato de seus familiares, assim como da avaliação de especialistas que os entendam bem (MARSH, 2021). Não há nenhum teste laboratorial que possa diagnosticar definitivamente a doença dissociativa, porém existem alguns testes psicológicos onde esse diagnóstico pode ser concluído, como por exemplo o Método de Rorschach e o Teste de Pfister.…”
Section: A Discussão Entre a Psicologia E A Psiquiatria Quanto Ao Dia...unclassified
“…The presence of significant differences between patients with DID and healthy simulators varied by research topic. Tests of implicit memory showed similar performances between groups (Huntjens et al, 2012(Huntjens et al, , 2014(Huntjens et al, , 2016Marsh et al, 2021Marsh et al, , 2018. In contrast, people with DID tended to show unique profiles on specialized clinical measures such as the Structured Interview of Reported Symptoms , the Structured Inventory of Malingered Symptoms (Brand et al, 2021), the Trauma Symptom Inventory (Palermo and Brand, 2019), the Test of Memory Malingering (Brand et al, 2019b), and the Minnesota Multiphasic Personality Inventory (Brand and Chasson, 2015;Brand et al, 2016c).…”
Section: Research Topicsmentioning
confidence: 94%
“…Some scholars have argued that there exist amnestic barriers between personality states resulting in an inability to recall traumatic events from certain identities (e.g., Dalenberg et al, 2012). However, research has shown that there actually is transfer of autobiographical memories between or across different personality states, rendering the idea of traumatic memory loss unlikely (Huntjens et al, 2012; see also Marsh et al, 2021). Critics contend that DID and dissociative amnesia may be fueled, perhaps even iatrogenically created or embellished, by widely prevalent sociocultural dramatizations of dissociative amnesia that are promoted and reinforced by the media (e.g., books, movies, television, Internet) and therapists (e.g., Lilienfeld et al, 1999; see also Pope et al, 2006).…”
Section: Repression and Dissociationmentioning
confidence: 99%